PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU MEDIA KONKRIT DALAM UPAYA PENINGKATAN PROSES DAN HASIL BELAJAR MUATAN IPA TEMA7 SUBTEMA 1 KELAS 4 - Buda, Chinda Hibatul (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
ABSTRACTThe research was carried out in order to improve the processes and outcomes of learning with media concrete on the charge on IPA Theme 7 subtema 1. The research was carried out on May 7-May 16, 2018 at 4th grade Student Affairs Tegalrejo 01 school year 2017/2018. This type of research using research action class. The percentage of observations of teachers has increased from 53% to cycle pre 72.5% in cycle I and 85.5% in cycle II. Students experience increased activity of pre cycle 51.67% to 71.66% in cycle I and 86.5% in cycle II. Student learning outcomes on pre cycle amounted to 11 students with a percentage of 40.74%, and not completely 16 students with percentages of 59.26%. After doing a repair on the cycle I increase that is 19 students complete with a percentage of 70.37% and 8 students not finished with a percentage of 29.63%, the result of the repair cycle I have yet to achieve the attainment of indicators i.e. 80% ketuntasan, then in to perform a repair cycle II. After the execution of the cycle II an increase inÂ  23 students finished with a percentage of 85.19% whereas students who do not complete amounted to 14.81 percentage people with 4%. Thus improvements with the Model of Problem Based Learning with concrete media can say successful because the results of learning objectives i.e. the percentage of 80%.Keyword: Problem Based Learning, Concrete Media, processes and Outcomes of learning, science